ANALISIS ISI: DAMPAK STANDAR KECANTIKAN PADA FILM IMPERFECT: KARIER, CINTA & TIMBANGAN - Nurul Izzati Sekarwening (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
The purpose of this study is to find out the form, difference and how many beauty standard effects were shown up on Imperfect: Karier, Cinta Timbangan movie. The form of beauty standard effects that shown up on the movie have a different frequencies in the whole movie. The population of this research is the whole scene of Imperfect: Karier, Cinta Timbangan as many as 98 scenes. Coding between the coders based on coding book and coding guides that was made by the researcher. This research is using quantitative method and descriptive research. The data will use the one-way anova test for finding out the signification of the difference on beauty standard effects and table of frequency for finding out the form of beauty standard effects percentage on the whole scenes of the movie.